Handel in Krisenzeiten : Ägyptisch-mykenische Handelsbeziehungen in der Ramessidenzeit - Schiller, Birgit, (Archaeopress Publishing Ltd, 2018)
An overview of the sites of Mycenaean pottery finds in Egypt and Nubia, this text analyses data from more than forty locations and presents a historical context for the vessels and sherds discovered.